Psychiatric medicalization in university life (Colombia Medica, 2024)
In 2020, Lynn Cunningham and Wendy Ractliffe produced the documentary Medicating Normal. Based on the testimonies of four American citizens, the directors shed light on the growing prescription of psychotropic drugs for physical and psychological discomforts inherent to everyday life. These discomforts, quickly categorized under psychiatric diagnoses, legitimized the use of increasingly potent medications. The documentary invites critical reflection on the psychological, physical, and social consequences of this medicalization process, as evidenced by the experiences of its protagonists.Medicalization, particularly in the mental health field, can be analyzed through three main dimensions proposed by Desviat (2). First is the tendency to pathologize everyday experiences such as pain, sadness, dissatisfaction, frustration, or personal limitations. Second, the equation of risk factors with illness implies a reductionist view of health. Finally, expanding diagnostic boundaries leads to an excessive inclusion of human phenomena within clinical categories.This type of situation had already been denounced in 2010 by Allen Frances, chair of the task force that developed the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV). At that time, he expressed regret for contributing to the proliferation of diagnoses among specific populations, such as attention deficit hyperactivity disorder (ADHD). He warned of even greater risks in the fifth edition, where the influence of economic and institutional interests became more evident.Beyond the conclusions that point to the economic interests of the pharmaceutical industry and medical complicity—particularly among some psychiatrists—as noted by authors from various schools of thought, an additional point of reflection is worth considering: the place of subjective responsibility in coping with everyday discomfort, especially in contexts where competition, constant change, and high demands are the norm.